Chemoselective benzylic oxidation of alkyl-substituted aromatics with singlet molecular oxygen generated from trans-3, 5 hydroperoxy-3, 5 dimethyl-1, 2-dioxolan-3-yl ethaneperoxate. Issue 24 (17th December 2022) - Najminejad, Zohreh
Abstract: Chemoselective benzylic oxidation of alkyl-substituted aromatics to carbonyl compounds was efficiently achieved with singlet molecular oxygen generated from trans- 5-hydroperoxy-3, 5-dimethyl-1, 2-dioxolane-3-yl ethaneperoxate. The singlet molecular oxygen was generated in situ from fragmentation trans -5-hydroperoxy-3, 5-dimethyl-1, 2-dioxolane-3-yl ethaneperoxate in the presence of KOH. All the reactions proceeded smoothly at room temperature to afford the products in good-to-excellent yields within short reaction times. Also, the method is compatible with functional groups including, amines, sulfides, and allylic CH2 . Graphical Abstract: UF0001